Cognitive dysfunction in active and remitted Egyptian non-neuropsychiatric systemic lupus erythematosus patients - Shorub, Eman M.; El-Azizi, Noran O.; Sabry, Moshria H.; Shalash, Ali S. (Middle East Current Psychiatry, 2014)
BACKGROUNDFew studies reported mild cognitive deficits in patients with non-neuropsychiatric systemic lupus erythematosus (non-NPSLE) with no consistent pattern of cognitive deficits. The aim of the study was to determine the pattern of cognitive dysfunction in non-NPSLE Egyptian patients in both active and remission states by applying a battery of neuropsychological tests. PATIENTS AND METHODSFifty patients with non-NPSLE (25 patients in activity and 25 patients in remissions) were evaluated for cognitive dysfunction and compared with 25 healthy controls matched for age, sex, and education. The activity of systemic lupus erythematosus disease was assessed. Each participant was subjected to clinical (general, neurological, and psychiatric) assessment, laboratory evaluation, and a battery of neuropsychological tests for assessing the cognitive functions. RESULTSCompared with controls, non-NPSLE patients in remission had worse cognitive domains of working memory, visual–constructional abilities, and executive function (P<0.005). The active group showed poorer performance in specific areas of cognitive function than the remission group at the time of testing, including working, short, and recent memory (P<0.001), logical reasoning, perception, sustained attention (P=0.003), visuoconstructional abilities (P=0.001), and executive function (P<0.001). Furthermore, cognitive impairment was significantly correlated with disease activity measured by Systemic Lupus Activity Measure score. CONCLUSIONPatients with non-NPSLE suffered from dysfunction of multiple cognitive domains that could be detected by neuropsychological tests. Moreover, cognitive dysfunctions worsen and expand in patients with active disease and are correlated mainly to disease activity.